2010
DOI: 10.2193/2009-131
|View full text |Cite
|
Sign up to set email alerts
|

Feral Swine Behavior Relative to Aerial Gunning in Southern Texas

Abstract: Feral swine (Sus scrofa) impact resources through their destructive feeding behavior, competition with native wildlife, and impacts to domestic animal agriculture. We studied aerial gunning on feral swine to determine if aerial gunning altered home range and core area sizes, distances between home range centroids, and distances moved by surviving individuals. We collected data before, during, and after aerial gunning in southern Texas. Using Global Positioning System collars deployed on 25 adult feral swine at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 17 publications
(17 reference statements)
2
39
1
Order By: Relevance
“…Campbell et al (2010) found that feral swine core and home range sizes did not differ before and after aerial gunning in Texas; however, movement rates increased during the gunning phase. Although this removal activity was only applied once to collared feral swine, these findings support our first removal activity results.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Campbell et al (2010) found that feral swine core and home range sizes did not differ before and after aerial gunning in Texas; however, movement rates increased during the gunning phase. Although this removal activity was only applied once to collared feral swine, these findings support our first removal activity results.…”
Section: Discussionmentioning
confidence: 83%
“…Hunting with dogs has been used to reduce feral swine populations around the world (Katahira et al 1993;Maillard and Fournier 1995;Parkes et al 2010) and is a popular recreational activity in the USA (Dickson et al 2003). Rapid eradication of feral swine can also be achieved through aerial shooting (Hone 1983;Choquenot et al 1999;Parkes et al 2010), although success is impacted by overstory vegetation types and ability to locate feral swine (West et al 2009;Campbell et al 2010;Massei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance range around each piggery for this sampling activity was based on documented feral pig home ranges (Saunders and Kay 1996, Dexter 1999, Mitchell and others 2009). Aerial shooting occurred two months prior to commencement of trapping, and was likely to have only minimal short-term impact on the remaining feral pig population (Campbell and others 2010). The remainder was trapped within 5 km of either piggery (n=50) using swing door box pig traps (BLASK Engineering, Australia), and then 43 were shot and seven collared and released.…”
Section: Methodsmentioning
confidence: 99%
“…Despite high levels of curiosity in domestic pigs (Wood-Gush and Vestergaard 1991;Kittawornrat and Zimmerman 2011), wild pigs are highly sensitive to changes in their environment and often alter their behaviors in response to new objects (Muir and McEwen 2007;Campbell et al 2010). Additionally, commonly used attractants (e.g., corn) oftentimes appeal to non-target species resulting in increased costs and missed opportunity (e.g., tripped traps).…”
Section: Introductionmentioning
confidence: 99%